Natural Killer and CD8 T Cells Contribute to Protection by Formalin Inactivated Respiratory Syncytial Virus Vaccination under a CD4-Deficient Condition - Ko, Eun-Ju (Immune Netw, 2020)
Respiratory syncytial virus (RSV) causes severe pulmonary disease in infants, young children, and the elderly. Formalin inactivated RSV (FI-RSV) vaccine trials failed due to vaccine enhanced respiratory disease, but the underlying immune mechanisms remain not fully understood. In this study, we have used wild type C57BL/6 and CD4 knockout (CD4KO) mouse models to better understand the roles of the CD4 T cells and cellular mechanisms responsible for enhanced respiratory disease after FI-RSV vaccination and RSV infection. Less eosinophil infiltration and lower pro-inflammatory cytokine production were observed in FI-RSV vaccinated CD4KO mice after RSV infection compared to FI-RSV vaccinated C57BL/6 mice. NK cells and cytokine-producing CD8 T cells were recruited at high levels in the airways of CD4KO mice, correlating with reduced respiratory disease. Depletion studies provided evidence that virus control was primarily mediated by NK cells whereas CD8 T cells contributed to IFN-γ production and less eosinophilic lung inflammation. This study demonstrated the differential roles of effector CD4 and CD8 T cells as well as NK cells, in networking with other inflammatory infiltrates in RSV disease in immune competent and CD4-deficient condition.